2020
DOI: 10.1007/s11869-020-00940-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of nationwide lockdown due to COVID-19 outbreak on air quality in Bangladesh: a spatiotemporal analysis

Abstract: In Bangladesh, a nationwide lockdown was imposed on 26 March 2020, due to the COVID-19 pandemic. Due to restricted emissions, it was hypothesized that the air quality has been improved during lockdown throughout the country. The study is intended to assess the impact of nationwide lockdown measures on air quality in Bangladesh. We analyzed satellite data for four different air pollutants (NO 2 , SO 2 , CO, and O 3) to assess the changes in the atmospheric concentrations of pollutants in major cities as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 48 publications
7
51
0
Order By: Relevance
“…The analysis showed that the six Emirates experienced a decline in NO 2 levels because of restricted transportation and factories' closure. This result is compatible with other earlier studies undertaken in various regions around the globe ( Baldasano, 2020 ; Dantas et al, 2020 ; Islam et al, 2020 ; Kaplan and Avdan, 2020 ; Sharma et al, 2020 ). Fig.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…The analysis showed that the six Emirates experienced a decline in NO 2 levels because of restricted transportation and factories' closure. This result is compatible with other earlier studies undertaken in various regions around the globe ( Baldasano, 2020 ; Dantas et al, 2020 ; Islam et al, 2020 ; Kaplan and Avdan, 2020 ; Sharma et al, 2020 ). Fig.…”
Section: Resultssupporting
confidence: 94%
“…These results are in accordance with the results of previously published research. Islam et al (2020) recorded identical outcomes for Bangladesh, Agarwal et al (2020) recorded an average reduction in NO 2 during the lockdown in China by 49% and in Mumbai (India) by more than 76%. In the Middle East (Morocco), NO 2 levels were decreased during the lockdown phase as well ( Sekmoudi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The air pollution associations revealed in this study were similar to that of prior studies in USA (Liang et al 2020). A higher value of CFR and PCD was significantly associated with exposure to NO 2 , but not O 3 and PM 2.5 (Liang et al 2020;Anil and Alagha 2020;Islam et al 2020). On the other hand, Wu et al 2020 showed that only 1 μg/m 3 increase in PM 2.5 was associated with an eighth percent increase in the COVID-19 death rate.…”
Section: Resultssupporting
confidence: 88%